Association between Septoria tritici Blotch, Plant Height, and Heading Date in Wheat - Simón, María Rosa (2005)
The relationship between resistance to Septoria tritici blotch with plant height and heading date has been in most cases attributed to genetic associations. More efficient selection for higher levels of quantitative resistance may result if the nature of the association between susceptibility with earliness and shortness can be determined. Genetic resistance to Septoria tritici blotch and its relationships with plant height and heading date were recorded in 50 Argentinean wheat (Triticum aestivum L.) cultivars in three environments (two in the field and one in the greenhouse) with one virulent isolate of Mycosphaerella graminicola (Fuckel) Schroeter, in Cohn (anamorph Septoria tritici Rob. ex Desm.). Furthermore, a set of 16 cultivars was tested with seven isolates of M. graminicola in the greenhouse at the adult stage. Cultivars varied greatly in resistance to the disease and plant material was identified with moderate to high levels of resistance to several isolates. The field and greenhouse experiments demonstrated no evidence of genetic associations between plant height, heading date, and resistance, indicating that selection of early and short lines with high levels of quantitative resistance is possible. The relationships between those traits were mainly caused by environmental and epidemiological factors, which indicates that management of cultivars should be optimized to minimize these associations.